Genetic mapping of microsatellite markers around the arcelin bruchid resistance locus in common bean - Blair, Matthew W.; Muñoz, C.; Buendía Castellanos, Hector F.; Flower, J; Bueno Mondragon, J.M.; Cardona Mejía, César (Springer, 2010)
The deployment in common beans (Phaseolus vulgaris L.) of arcelin-based bruchid resistance could help reduce post-harvest storage losses to the Mexican bean weevil [(Zabrotes subfasciatus (Boheman)]. Arcelin is a member of the arcelin-phytohemagglutinin-?-amylase inhibitor (APA) family of seed proteins, which has been extensively studied but not widely used in bean breeding programs. The purpose of this study was to evaluate microsatellite markers for genetic analysis of arcelin-based bruchid resistance and to determine the orientation of markers and the rate of recombination around the APA locus. A total of 10 previously developed microsatellites and 22 newly developed markers based on a sequenced BAC from the APA locus were screened for polymorphism and of these 15 were mapped with an F2 population of 157 individuals resulting from a susceptible × resistant cross of SEQ1006 × RAZ106 that segregated for both the arcelin 1 allele and resistance to the bruchid, Z. subfasciatus. Microsatellites derived from APA gene sequences were linked within 0.8 cM of each other and were placed relative to the rest of the b04 linkage group. In a comparison of genetic to physical distance on the BAC sequence, recombination was found to be moderate with a ratio of 125 kb/cM, but repressed within the APA locus itself. Several markers were predicted to be very effective for genetic studies or marker-assisted selection, based on their significant associations with bruchid resistance and on low adult insect emergence and positions flanking the arcelin and phytohemagglutinin genes.